Electron tomography of plasmodium falciparum merozoites reveals core cellular events that underpin erythrocyte invasion - Hanssen, Eric; Cyrklaff, Marek; Frischknecht, Friedrich (Cellular microbiology, 2013)
Erythrocyte invasion by merozoites forms of the malaria parasite is a key step in the establishment of human malaria disease. To date, efforts to understand cellular events underpinning entry have been limited to insights from non-human parasites, with no studies at sub-micrometer resolution undertaken using the most virulent human malaria parasite, Plasmodium falciparum. This leaves our understanding of the dynamics of merozoite sub-cellular compartments during infectionincomplete, in particular that of the secretory organelles. Using advances in P. falciparum merozoite isolation and new imaging techniques we present a three-dimensional study of invasion using electron microscopy, cryo-electron tomography and cryo-X-ray tomography. We describe the core architectural features of invasion and identify fusion between rhoptries at the commencement of invasion as a hitherto overlooked event that likely provides a critical step that initiates entry. Given the centrality of merozoite organelle proteins to vaccine development, these insights provide a mechanistic framework to understand therapeutic strategies targeted towards the cellular events of invasion.